The Effect of the Project-Based Learning Model on the Circulatory System Topic Toward Students’ Learning Outcomes and Creative Thinking Ability in Class XI - Rizaldi, Muhammad; Putra, Aminuddin Prahatama; Amintarti, Sri (Universitas Khairun, 2025)
This study aims to evaluate the impact of using the Project Based Learning (PjBL) model in teaching the Circulatory System material on the learning outcomes and creative thinking abilities of 11th-grade students at SMA Negeri 8 Banjarmasin. The objectives of the research include: (1) assessing the influence of implementing the PjBL model on students' learning outcomes, (2) evaluating the impact of applying the PjBL model on students' creative thinking abilities. The research employed a quasi-experimental method with a posttest nonequivalent control group design. Class XI 8 was selected as the experimental group implementing the PjBL model, while Class XI 10 served as the control group using the Direct Instruction model. Data were collected through test and non-test techniques, and data analysis utilized the Mann-Whitney nonparametric test and descriptive analysis. The findings of the study reveal that: (1) There is no significant influence of implementing the PjBL model on the Circulatory System material on the learning outcomes of 11th-grade students at SMA Negeri 8 Banjarmasin, with an Asymp.Sig. (2-tailed) value of 0.335. (2) There is a significant impact of applying the PjBL model on the Circulatory System material on the creative thinking abilities of the students, with an Asymp.Sig (2-tailed) value of 0.000.